Incidencia del consumo de agua envasada en la salud pública de la ciudad de Calceta, Manabí-Ecuador - Santana Quiroz, Diego Estéfano (2021)
The objective of the research was to evaluate the incidence of bottled water consumption on public health in Calceta city. Interviews were conducted with health professionals and a survey of the inhabitants of the city in order to collect information on gastrointestinal diseases that have occurred due to the consumption of water, where 7 samples were collected from different brands of water with the highest consumption that are sold in the city, the physicochemical and microbiological quality of the bottled water was evaluated in an interval of 21 days for 3 occasions, the general results obtained from the physicochemical parameters showed that 83% of the analyzed samples complied with the INEN STANDARD 2200: 2008; 17% did not comply; likewise, for the results of the microbiological parameters, 57% did not comply with the aforementioned norm and 43% did, where the analyzed samples exceeded the norm for the count of mesophilic aerobes, Escherichia coli and coliforms. Information was also obtained from the Aníbal González hospital on gastrointestinal diseases caused by these pathogenic microorganisms in the population, directly associated with drinking water, from 2014 to the present. A correlation was developed where a positive relationship was found between the consumption of bottled water and the frequency of occurrence of gastrointestinal diseases in person per year, determining that the bottled water that is sold in Calceta city has a significant negative effect on public health.